Antibacterial and Toxicity Activity from Non Polar Fraction of Gal Manjakani (Quercus infectoria) - iin asparinda; Tita Juwitaningsih (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2020)
Gal manjakani (Quercus infectoria) is one of the most popular medicinal plants in Asia. This plant is found in Turkey, Syria, Persia, Cyprus, and Greece. This study aims to determine the compounds contained in the non-polar fraction and to determine the antibacterial activity and toxicity of the fraction. Gal Manjakani was extracted by maceration method with acetone then fractionated with n-hexane, ethyl acetate and methanol. Non-polar fractions were analyzed using Gas Chromatography-Mass Spectroscopy (GCMS). The antibacterial activity test used disc diffusion and microdilution methods based on the CLSI standard method against Staphylococcus aureus and Escherichia coli bacteria. Toxicity test was conducted using the Brine Shrimp Lethality Test (BSLT) method. The GC-MS identification results showed that the non-polar fraction of gal manjakani contained 27 compounds, with the main compounds being cis-vaccenic acid = 35,19%, n-hexadecanoic acid = 16,66%, 1-heptadecanecarboxylic acid = 5,03%, dodecanoic acid = 4.73%, bis (2-ethylhexyl) phthalate = 4,35%, hexadecanoic acid, methyl ester = 2,14% and tetradecanoic acid = 1,31%. The results of the antibacterial activity test showed activity with an inhibition zone of 6.26 ± 0.6 mm against S.aureus bacteria and 8.23 ​​± 0.21 mm against E.coli bacteria, with a percentage of effectiveness against S.aureus bacteria of 15.34% and for E. coli 44.24%. The MIC and MBC values ​​of S.aureus bacteria were> 5000 (µg / mL) and> 5000 (µg / mL) and E. coli was 312.5 (µg / mL) and> 5000 (µg / mL). The results of the toxicity test showed that the non-polar fraction of gal Manjakani was toxic with an LC50 value of 2.1527 ppm.